Efficacy of Intraventricular Sponge Placement to Capture Debris in Aortic Valve Replacement. Issue 3 (May 2022) - Purrman, Kyle C.; Ndikumana, Eric; Amirjamshidi, Hossein; Syposs, Chauncey; Vidovich, Courtney; Boyce, Brendan; Knight, Peter
Objective: Surgical aortic valve replacement (SAVR) carries the known risk of shedding debris into the left ventricle during valve leaflet excision and annulus debridement. Embolization of this debris may have devastating effects for the patient. Although surgeons have developed methods to mitigate this risk, no data exist as to their efficacy. Herein, we present the first study that evaluates the efficacy of a technique for capturing debris during SAVR.Methods: Our group conducted a prospective case series of 20 patients who underwent SAVR using the insertion of an intraventricular surgical sponge prior to valve leaflet excision and annulus debridement to capture debris. Surgical sponges were grossly, radiographically, and histologically examined for the presence of cellular and acellular debris to determine the efficacy of this technique.Results: Of the 20 surgical sponges analyzed, 15 specimens (75%) registered positivity for cellular and/or acellular debris. Seven sponges (35%) were grossly positive, 15 sponges (75%) were radiographically positive, and 4 sponges (20%) were histologically positive for calcified debris on examination.Conclusions: This is one of the few studies to objectively evaluate a method used to capture debris in SAVR procedures. Our results demonstrate a high frequency of debris captured within intraventricular surgical sponges and confirms the efficacy of this technique. While these data are promising, numerous additional approaches exist to capture debris, and a best practice standard should exist across the specialty.  In addition, this study does not address the clinical outcomes associated with this technique. To these ends, additional data and multicenter collaboration are required.